2001
DOI: 10.1074/jbc.m100380200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Interferon and Retinoic Acid-induced Cell Death Activation through Thioredoxin Reductase

Abstract: Interferons (IFNs) and retinoids are potent biological response modifiers. The IFN-␤ and all-trans-retinoic acid combination, but not these single agents individually, induces death in several tumor cell lines. To elucidate the molecular basis for these actions, we have employed an antisense knockout approach to identify the gene products that mediate cell death and isolated several genes associated with retinoid-IFN-induced mortality (GRIMs). One of the GRIM cDNAs, GRIM-12, was identical to human thioredoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 72 publications
2
34
0
Order By: Relevance
“…Loss of permeability of the mitochondrial membrane results in a release of apoptogenic proteins -including cytochrome c (Kluck et al, 1997;Liu et al, 1996), which is required for the activation of caspase-9. In our earlier studies, we have shown activation of caspase-9 (Angell et al, 2000;Ma et al, 2007) and cytochrome-c release in response to IFN/RA (Ma et al, 2001). In this study, we have shown that mutant caspase-9 and Bcl2 block the processing of GRIM-1.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Loss of permeability of the mitochondrial membrane results in a release of apoptogenic proteins -including cytochrome c (Kluck et al, 1997;Liu et al, 1996), which is required for the activation of caspase-9. In our earlier studies, we have shown activation of caspase-9 (Angell et al, 2000;Ma et al, 2007) and cytochrome-c release in response to IFN/RA (Ma et al, 2001). In this study, we have shown that mutant caspase-9 and Bcl2 block the processing of GRIM-1.…”
Section: Discussionmentioning
confidence: 73%
“…GRIM-12 was required for keeping the active sites of caspases in reduced state through its substrate thioredoxin (Ma et al, 2001). The second protein, GRIM-19, inhibits transcription factor STAT3 (Zhang et al, 2003), a protein known to upregulate the expression of mitochondrial antiapoptotic regulators Bcl2, Bcl-X L and Mcl-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because STAT3 is known to activate the genes involved in cell proliferation and inhibition of apoptosis, the GRIM-19 effects on STAT3C-induced cell growth are probably exerted through an inhibition of these processes. These results are consistent with other reports that the fas gene is repressed by STAT3 (36) and IFN/RA treatment induces Fas and Fas ligand expression in cells (37), which can suppress tumor growth. Indeed, the presence of GRIM-19 augmented Fas-mediated apoptosis in the S3C-expressing cells (see Supplementary Fig.…”
Section: Discussionsupporting
confidence: 83%